Prospective geo-modeling in cardiac surgery with extra-corporeal circulation-partial assessment at the Lille University Hospital - Anne Quesnel-Barbet; Julien Soula; Frédéric Albert; Arnaud Hansske; Gilles Maignant (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Faced with the imminent opening of the new competing "Lens/Bois-Bernard" care unit in the Nord - Pas-de-Calais region (4 million inhabitants), a prospective modeling study was carried out in 1999 in response to a request from the Lille University Hospital (LUH), which sought to estimate the positive or negative impact on its recruitment catchment areas and consequently on its 1996 cardiac surgery activity (comprising 2 care units, i.e., 84 beds). In 1996, only 3 care units with the "Clinique du Bois" in Lille showed our regional undersupply of cardiac surgery compared to the national average of 5.96 [1,2].